ANALISIS PENGARUH GAYA KEPEMIMPINAN, DISIPLIN KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN DI PT. SUNAN DRAJAT LAMONGAN - Ahmad Yani Syaikhudin; Ariefah Sundari; Ahmad Fathur Rozi (J-MACC, 2023)
ABSTRACT In the current era of globalization, almost all companies follow business competition that needs to be tight this is done for competitive competition, this is where the role of human resources will compete for quality and performance capacity to find out otherwise or vice versa. Research conducted to understand leadership style, work discipline and the environment on the performance of employees at PT. Sunan Drajat Lamongan. This research is a quantitative research. The population in this study is the company PT. Sunan Drajat Lamongan with 50 respondents. This research data analysis technique uses multiple linear regression analysis. The results showed that (1) leadership style had a significant effect on employee performance at PT. Sunan Drajat Lamongan. (2) Significant work discipline on employee performance at PT. Sunan Drajat Lamongan. (3) The work environment is significant on the performance of employees at PT. Sunan Drajat Lamongan. (4) simultaneously leadership style, work discipline and work environment significantly influence employee performance at PT. Sunan Drajat Lamongan.